EFL STUDENTS' PERCEPTION ON PLAGIARISM IN ACCOMPLISHING THESIS AT UNIVERSITAS ISLAM MALANG - Muhammad Nur Khuzaini; Ali Ashari; Nuse Aliyah Rahmati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Plagiarism has become one form of cheating that occurs in the academic system. Some students do plagiarism by their intelligent ways, for example by changing some grammatical structures. This study focused on knowing the students' perception. In writing with sources, plagiarism defined as the act of admission. The thesis is a scientific work written by undergraduate students on the subject of a specific topic or field. This study is a tool for providing multidimensional data required to gain an understanding of students' perception of plagiarism in the completion of the thesis. This research conducted through a questionnaire to collect the data needed. Some people think plagiarism is not good, and some think it is positive because plagiarism helps students finish their thesis. English Department students at Universitas Islam Malang did plagiarism. Plagiarism may also be positive or negative as plagiarism allows them to accomplish their tasks. Reasons include lack of motivation, laziness and less honesty.Â Key Words: Plagiarism, Perceptions, Thesis